Radiation dose-event relationship after intraoperative radiotherapy as a boost in patients with breast cancer - Cho, Yeona; Kim, Jun Won; Chang, Jee Suk; Kim, Ji Young; Ahn, Sung Gwe; Bae, Soong June; Jeong, Joon; Lee, Ik Jae (Frontiers in Oncology, 2023)
Purpose: Intraoperative radiotherapy (IORT) can be used as a boost in combination with external whole breast irradiation. This study reports the clinical and dosimetric factors associated with IORT-related adverse events. Methods and Materials: Between 2014 and 2021, 654 patients underwent IORT. A single fraction of 20 Gy was prescribed to the surface of the tumour cavity using the mobile 50-kV X-ray source. For skin dose measurement, at least four optically stimulated luminescent dosimeter (OSLD) chips were annealed and attached to the skin edge in the superior, inferior, medial, and lateral locations during IORT. Logistic regression analyses were conducted to identify factors associated with IORT-related AE. Results: With a median follow-up period of 42 months, 7 patients experienced local recurrence, resulting in a 4-year local failure-free survival rate of 97.9%. The median skin dose measured by OSLD was 3.85 Gy (range, 0.67–10.89 Gy), and a skin dose of > 6 Gy was observed in 38 patients (2%). The most common AE was seroma (90 patients, 13.8%). We also found that 25 patients (3.9%) experienced fat necrosis during follow-up, and among them, 8 patients underwent biopsy or excision to exclude local recurrence. IORT-related late skin injury occurred in 14 patients, and a skin dose > 6 Gy was significantly associated with IORT-induced skin injury (odds ratio 4.942, 95% confidence interval 1.294–18.871, p = 0.019). Conclusions: IORT was safely administered as a boost to various populations of patients with breast cancer. However, several patients may experience severe skin injuries, and for older patients with diabetes, IORT should be performed with caution.